2017
DOI: 10.1097/md.0000000000006281
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic obstructive pulmonary disease and hemorrhoids

Abstract: According to traditional Chinese medicine (TCM) theory, a specific physiological and pathological relationship exists between the lungs and the large intestine. The aim of this study is to delineate the association of chronic obstructive pulmonary disease (COPD) and hemorrhoids in order to verify the “interior–exterior” relationship between the lungs and the large intestine. A retrospective cohort study is conceived from the National Health Insurance Research Database, Taiwan. The 2 samples (COPD cohort and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
1
Order By: Relevance
“…Among 1079 patients, 74 presented with a new diagnosis of HD (6.9% or 69 per 1000 persons) [ 5 ]. Lin et al reported on the new HD diagnosis (International Classification of Diseases, Ninth Revision, Clinical Modification: 455) among patients with and without chronic obstructive pulmonary disease (COPD) as reported in a Taiwanese national database between 2000 and 2003 and followed up until 2011 [ 9 ]. Overall incidence among patients with COPD was approximately 1.6 times greater than in patients without COPD (average annual incidence 11.5 vs. 7.1 per 1000 person-years) [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 1079 patients, 74 presented with a new diagnosis of HD (6.9% or 69 per 1000 persons) [ 5 ]. Lin et al reported on the new HD diagnosis (International Classification of Diseases, Ninth Revision, Clinical Modification: 455) among patients with and without chronic obstructive pulmonary disease (COPD) as reported in a Taiwanese national database between 2000 and 2003 and followed up until 2011 [ 9 ]. Overall incidence among patients with COPD was approximately 1.6 times greater than in patients without COPD (average annual incidence 11.5 vs. 7.1 per 1000 person-years) [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall incidence among patients with COPD was approximately 1.6 times greater than in patients without COPD (average annual incidence 11.5 vs. 7.1 per 1000 person-years) [ 9 ]. These findings were consistent between men and women, and across different age groups [ 9 ]. Neither study was designed specifically to measure HD incidence in the general population, and thus estimates are likely to be imperfect.…”
Section: Resultsmentioning
confidence: 99%
“…Einen genetischen Hintergrund vermutet man schon lange, und rezente Studien zeigen auch einen deutlichen Hinweis hierfür [13,14]. Nicht zuletzt deswegen werden aus Hämorrhoiden-Studien zunehmend Patienten mit assoziierten Erkrankungen, wie genetischen Bindegewebserkrankungen, chronisch-obstruktiver Lungenerkrankung (COPD) oder Gefäßerkrankungen, Herniationen und genitourethralem Prolaps, ausgeschlossen [3, 11,12].…”
Section: » Die Prolapstheorie Hat Sich Als Die Gängigste Hypothese Duunclassified
“…It is characterized by clusters of vascular tissues, smooth muscles and connective tissues which occur due to abnormal dilatation of the vascular channel and pathological changes within the anal cushions [3,4]. Although the etiology underlying the development of hemorrhoids has not been completely elucidated, increased intra-abdominal pressure during pregnancy or straining may be the cause venous engorgement of the hemorrhoidal plexus [5,6]. Patients who suffer from hemorrhoids experience bleeding, fecal soiling, pruritus etc., which strongly affects their quality of life [7].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who suffer from hemorrhoids experience bleeding, fecal soiling, pruritus etc., which strongly affects their quality of life [7]. While internal hemorrhoids are often painless, external hemorrhoids are associated with significant pain and discomfort due to activation of perianal innervations associated with thrombosis [3,5].…”
Section: Introductionmentioning
confidence: 99%